Toko Kelontong Tradisional Dalam Era Teknologi Bisnis Digital - Timotius Hernika Putra (Jurnal Publikasi Ilmu Manajemen, 2023)
The grocery store business sector, or more precisely, namely conventional stores, is currently experiencing various growths, both the number of shops and the variety of goods it sells are experiencing growth. But from the other side, there are also shops that sell their wares not through the physical form of shop buildings, and they take advantage of technological developments, such as the use of smartphones in running their business, or we can say now online shops. Apart from all that, the business of using an online store can be considered quite promising because the seller does not need to open a physical store and spend money to open the store, but they can still trade only from home and market it through existing digital storefronts. This. With this online store application, there are also positive and negative sides, especially if we are dealing with grocery stores that still exist today. Based on what was discussed, the authors used a qualitative research methodology, because this research is very compatible with the research method and easy to describe according to the opinions of informants. Based on the results that the authors have obtained from these informants, many of them really like online shopping, be it for their grocery store needs to their own personal needs, but not a few also complain because the emergence of this online shop has actually made the shop business sector Their grocery store experienced a decrease in the number of customers and what happened most often, according to the informants, was that the goods that did not arrive were what was wanted.